Structural, spectroscopic, electronic, nonlinear optical and thermodynamic properties of a synthesized Schiff base compound: A combined experimental and theoretical approach - Gokce, Halil; Ozturk, Nuri; Kazici, Mehmet; Goreci, Cigdem Yorur; Gunes, Serap (ELSEVIER, 2017)
A Schiff base compound, 2-[(1H-benzimidazol-2-ylimino)methy1]-4-bromophenol (BISB), was synthesized and its spectroscopic characterization was performed using experimental methods such as FT-IR, Raman, proton and carbon -13 NMR chemical shifts and UV Vis. spectroscopies. Density functional theory (DFT/B3LYP/6-311G(d,p)) computations were used to investigate the optimized molecular geometry, conformational forms, harmonic vibrational wavenumbers, NMR chemical shifts, UV Vis. spectroscopic parameters, natural bond orbital (NBO) analysis, HOMO-LUMO energies, nonlinear optical (NLO) properties, molecular electrostatic potential (MEP) map, atomic charges and thermodynamic properties of the BISB molecule. The assignments of vibrational modes were performed by means of potential energy distribution (PED) using VEDA4 program, The NBO analysis was used to investigate intramolecular hyrogen bonding (O-H center dot center dot center dot N), bond species, hyperconjugation interactions and intramolecular charge transfers (ICTs). Considering the computed HOMO and LUMO energies, the quantum molecular descriptors such as ionization potential (I), electron affinity (A), chemical hardness (eta), chemical softness (zeta), electronegativity (chi), chemical potential (mu) and electrophilicity index (omega) parameters were investigated for the BISB molecule. DFT computations were also performed to determine the dipole moment (mu) the mean polarizability (alpha), the anisotropy of the polarizability (Delta alpha) and the first hyperpolarizability (beta(0)) values. The recorded experimental spectroscopic results are in a good harmony with the computed data. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Vibrational spectroscopy; NMR chemical shifts; Electronic properties; DFT computations; NLO analysis; Thermodynamic properties; BROMOBENZENE DERIVATIVES; CRYSTAL-STRUCTURE; FT-IR; SPECTRA; NMR; DFT; CHLOROBENZENE; Chemistry